Reflux Incidence among Exclusively Breast Milk Fed Infants: Differences of Feeding at Breast versus Pumped Milk - Jennifer Yourkavitch; Sabrina Zadrozny; Valerie L. Flax (MDPI AG, 2016)
The practice of feeding infants expressed breast milk is increasing in the United States, but the impacts on infant and maternal health are still understudied. This study examines the monthly incidence of regurgitation (gastro-esophageal reflux) in exclusively breast milk fed infants from ages two to six months. Among infants whose mothers participated in the Infant Feeding Practices II Study (IFPS II; 2005-2007), data on reflux and feeding mode were collected by monthly questionnaires. A longitudinal, repeated measures analysis was used, with feeding mode lagged by one month in order to compare reflux incidence among infants fed directly at the breast to infants receiving pumped breast milk. Mothers in both feeding groups had similar characteristics, although a greater proportion feeding at least some pumped milk were primiparous. The number of exclusively breastfed infants decreased steadily between months 2 and 6, although the proportion fed at the breast remained similar over time. An association between feeding mode and reflux incidence was not found; however, the analyses were limited by a small number of reported reflux cases. More studies are needed to further explain the relationship between different feeding modes and infant reflux.